Golden Dimsum’s Word of Mouth Strategy in Increasing Sales During 2023 - 2024 - Farransahad, Bazlin Fania; Sudiwijaya, Erwan (Jogjakarta Communication Conference (JCC), 2025)
This research explores the implementation of word-of-mouth (WoM) marketing strategy by Golden Dimsum to enhance sales performance during the period of 2023–2024. The strategy was selected for its effectiveness, low cost, and ability to establish strong customer relationships. Utilizing a descriptive qualitative approach, data were obtained through interviews and documentation and analyzed using the Miles and Huberman interactive model. The results indicate that the WoM strategy was executed through five key dimensions: talkers, topics, tools, talking part, and tracking. Promotional messages were naturally disseminated by loyal customers, as well as the business owner's family and acquaintances. The most frequently discussed aspects included product taste, pricing, and service quality. Instagram and TikTok functioned as the primary communication platforms, supported by direct engagement from the owner. Continuous monitoring of customer comments and reviews was conducted to maintain satisfaction. The study concludes that WoM marketing effectively sustained sales and expanded market reach, suggesting its relevance as a strategic model for micro, small, and medium enterprises (MSMEs) in the digital era.